Increased expression and activity of brain cortical cPLA2 due to chronic lipopolysaccharide administration in mouse model of familial Alzheimer’s disease - Gynther, Mikko; Estrada, Mariana Leal; Loppi, Sanna; Korhonen, Paula; Kanninen, Katja M.; Malm, Tarja; Koistinaho, Jari; Auriola, Seppo; Fricker, Gert; Puris, Elena (Pharmaceutics, 2022)
Cytosolic phospholipase A2 (cPLA2) is an enzyme regulating membrane phospholipid homeostasis and the release of arachidonic acid utilized in inflammatory responses. It represents an attractive target for the treatment of Alzheimer’s disease (AD). Previously, we showed that lipopolysaccharide (LPS)-induced systemic inflammation caused abnormal lipid metabolism in the brain of a transgenic AD mouse model (APdE9), which might be associated with potential changes in cPLA2 activity. Here, we investigated changes in cPLA2 expression and activity, as well as the molecular mechanisms underlying these alterations due to chronic LPS administration in the cerebral cortex of female APdE9 mice as compared to saline- and LPS-treated female wild-type mice and saline-treated APdE9 mice. The study revealed the significant effects of genotype LPS treatment on cortical cPLA2 protein expression and activity in APdE9 mice. LPS treatment resulted in nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) activation in the cortex of APdE9 mice. The gene expressions of inflammation markers Il1b and Tnfa were significantly elevated in the cortex of both APdE9 groups compared to the wild-type groups. The study provides evidence of the elevated expression and activity of cPLA2 in the brain cortex of APdE9 mice after chronic LPS treatment, which could be associated with NFkB activation.
Gesehen am 27.02.2023